2012
DOI: 10.1099/ijs.0.031708-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene orders in the upstream of 16S rRNA genes divide genera of the family Halobacteriaceae into two groups

Abstract: In many prokaryotic species, 16S rRNA genes are present in multiple copies, and their sequences in general do not differ significantly owing to concerted evolution. At the time of writing, the genus Haloarcula of the family Halobacteriaceae comprises nine species with validly published names, all of which possess two to four highly heterogeneous 16S rRNA genes. Existence of multiple heterogeneous 16S rRNA genes makes it difficult to reconstruct a biological phylogenetic tree using their sequence data. If the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 29 publications
(43 reference statements)
3
25
0
Order By: Relevance
“…salarium B-1 T harbored the genes encoding, in order, nonhistone chromosomal protein MD1, dihydroorotate oxidase, valyl-tRNA synthetase, phenylalanyl-tRNA synthetase subunit ␣ and ␤, tryptophanyl-tRNA synthetase, tRNA intron endonuclease, DNA topoisomerase I, haloacid dehalogenase-like hydrolase, DEAD/DEAH box helicase, lipoic acid synthase, pyruvate dehydrogenase E1 component subunit ␣ and ␤, pyruvate dehydrogenase E2 component, and dihydrolipoamide dehydrogenase in the upstream of the 16S rRNA gene. This gene order was consistent with those of Haloferax volcanii DS2 and Halogeometricum borinquense DSM 11551 T (8), which supported their close relationship in the complete rpoB= gene-based phylogeny (5). More detailed analysis of the genome will provide further insight into the genomic differences with respect to other haloarchaea and metabolism of the extreme halophiles.…”
supporting
confidence: 73%
“…salarium B-1 T harbored the genes encoding, in order, nonhistone chromosomal protein MD1, dihydroorotate oxidase, valyl-tRNA synthetase, phenylalanyl-tRNA synthetase subunit ␣ and ␤, tryptophanyl-tRNA synthetase, tRNA intron endonuclease, DNA topoisomerase I, haloacid dehalogenase-like hydrolase, DEAD/DEAH box helicase, lipoic acid synthase, pyruvate dehydrogenase E1 component subunit ␣ and ␤, pyruvate dehydrogenase E2 component, and dihydrolipoamide dehydrogenase in the upstream of the 16S rRNA gene. This gene order was consistent with those of Haloferax volcanii DS2 and Halogeometricum borinquense DSM 11551 T (8), which supported their close relationship in the complete rpoB= gene-based phylogeny (5). More detailed analysis of the genome will provide further insight into the genomic differences with respect to other haloarchaea and metabolism of the extreme halophiles.…”
supporting
confidence: 73%
“…mukohataei Hmuk_R0017 (orthologue) and Hmuk_R0036 (Tindall et al, 2009), which makes it difficult to discuss phylogeny from a tree reconstructed from those heterogeneous sequence data. Recently, Minegishi et al (2012) found that the dihydroorotate oxidase gene, pyrD, was present immediately upstream of one 16S rRNA gene in each of ten members of the family Halobacteriaceae whose genome sequences have been determined, including species of the genera Haloarcula and Halomicrobium, as well as species of genera that possess a single rRNA operon. Minegishi et al (2012) suggested that the 16S rRNA genes were orthologous, and designed a PCR primer set to amplify DNA fragments encompassing a region from the conserved region of the pyrD gene to a conserved region of the 23S rRNA gene.…”
mentioning
confidence: 99%
“…Other genetic markers have been proposed in recent years for phylogenetic tree reconstruction for the members of the family by multilocus sequence analysis (Dennis and Shimmin 1997;Enache et al 2007a;Minegishi et al 2010aMinegishi et al , 2012aPapke et al 2007). Use of the markers atpB, EF-2, radA, rpoB 0 , and secY enabled differentiation of individual strains within species, as well as the delineation of species and genera, including the identification of potential novel species and even family-like relationships (Papke et al 2011).…”
Section: Phylogenetic Structure Of the Family And Its Generamentioning
confidence: 99%